Analisis Hierarki Memori Pada Organisasi Arsitektur Komputer - Ziliwu, Ifolala Natafati (CV. SINAR HOWUHOWU, 2025)
In computer architecture, memory plays an important role in overall system performance. Memory hierarchy is a concept that describes the grouping of memory based on access speed, size, and cost. This article aims to analyze the memory hierarchy in computer architecture organization, which includes registers, cache, main memory (RAM), and secondary storage. This analysis will look at how each memory level works to support processor efficiency and performance. The results of this research show that with the correct use of a memory hierarchy system, computer performance can be optimized by reducing latency and increasing throughput. This research also provides an overview of the challenges in memory design and solutions that can be implemented to improve system performance.